The synthesis of 1-butene oligomers with vinyl endgroups and their use in further reactions - Al-Aeeb, Ahmed (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.